Classifying ESG funds under SFDR: why Article 8 is more prevalent than Article 9 - Ratamo, Siiri (My University, 2025)
The European Union aims to shift capital toward sustainable economic activities as part of its broader climate and environmental goals. A central instrument in this effort is the Sustainable Finance Disclosure Regulation (SFDR), which requires investment funds to classify themselves under Articles 6, 8 or 9 based on their sustainability profile. Article 6 applies to products that only either consider ESG risks or explain why such risks are not relevant. Article 8 covers products that promote environmental or social characteristics and may include sustainable investments, but do not have sustainability as a core investment focus. Article 9 is reserved for products that make only sustainable investments and have a clear sustainability objective, making them most directly aligned with the EU\u2019s ambitions. Understanding how these categories are applied in practice is therefore essential for evaluating whether the SFDR is effectively supporting the allocation of capital in line with the EU\u2019s sustainability objectives. This thesis builds on that policy context by examining the factors that influence fund managers\u2019 classification decisions under the SFDR, particularly in cases where sustainability is a relevant consideration, but funds are still categorised under Article 8 rather than Article 9. In such cases, the choice of Article 8 often relates to its lower compliance demands and broader flexibility. The research is based on a qualitative case study of the Finnish market, using nine semi-structured interviews with professionals involved in fund categorisation. To support the analysis, the study draws on the neoclassical economic paradigm and the prosocial paradigm, which offer contrasting perspectives on how sustainability considerations are approached within financial institutions. The study produced several key findings. First, Article 9 is often avoided due to unclear definitions and concerns over legal and reputational risk. Second, its restrictive investment criteria are seen as incompatible with portfolio diversification and performance expectations. Third, weak demand for Article 9, particularly from retail investors who often cannot distinguish between the SFDR categories, further reduces the incentive to pursue it. In contrast, Article 8 is perceived as a safer and more commercially viable option, offering greater flexibility in how sustainability is defined and implemented. The findings highlight how current market structures and regulatory ambiguity may limit the effectiveness of the SFDR in fully achieving its intended sustainability impacts.

Euroopan unioni pyrkii ohjaamaan pääomaa kestävään taloudelliseen toimintaan osana laajempia ilmasto- ja ympäristötavoitteitaan. Keskeinen väline tässä pyrkimyksessä on kestävän rahoituksen tiedonantoasetus (SFDR), jonka mukaan sijoitusrahastot on luokiteltava 6, 8 tai 9 artiklaan kestävyysaspektien huomioimisen perusteella. Asetuksen artiklaa 6 sovelletaan tuotteisiin, joissa ainoastaan joko otetaan ESG-riskit huomioon tai selitetään, miksi tällaiset riskit eivät ole merkityksellisiä sijoitusprosessissa. Artikla 8 kattaa tuotteet, jotka edistävät sijoituspäätöksillään ympäristön ja yhteiskunnan kestävää kehitystä, mutta tämän ei tarvitse olla rahaston päätarkoitus. Artikla 9 koskee rahastoja, jotka tekevät ainoastaan kestäviä sijoituksia ja joilla on selkeä kestävän kehityksen edistämisen tavoite. Ne vastaavat siis suorimmin EU:n tavoitetta pääoman ohjaamisesta kestävyyttä edistäviin kohteisiin. Näiden luokkien käytännön soveltamisen ymmärtäminen on olennaista arvioitaessa, onnistuuko SFDR tehokkaasti tukemaan pääoman kohdentamista EU:n tavoitteiden mukaisesti. Tämä tutkielma pohjaa kyseiseen sääntelykehykseen ja tarkastelee niitä tekijöitä, jotka vaikuttavat rahastonhoitajien SFDR:n mukaisiin luokittelupäätöksiin. Tutkielmassa keskitytään erityisesti rahastoihin, joissa kestävyys on olennainen tekijä, mutta rahasto luokitellaan silti artiklan 8 eikä artiklan 9 mukaisesti. Tutkimus on Suomen markkinoille sijoittuva laadullinen tapaustutkimus, jonka empiirinen aineisto kerättiin yhdeksästä puolistrukturoidusta haastattelusta rahastojen luokitteluun osallistuvien ammattilaisten kanssa. Analyysin tukena tutkimuksessa hyödynnetään uusklassillisen taloustieteen paradigmaa ja prososiaalista paradigmaa, jotka tarjoavat erilaisia tulkintoja siitä, miten rahastoja tarjoavat yhtiöt lähestyvät kestävyysasioita. Tutkimus tuotti useita keskeisiä havaintoja. Ensinnäkin artikla 9:n mukaista luokistusta vältetään usein sen epäselvien määritelmien sekä oikeudellisten ja maineeseen liittyvien riskien vuoksi. Toiseksi sen tiukat sijoituskriteerit nähdään yhteensopimattomina sijoitussalkun hajauttamisen ja tuotto-odotusten saavuttamisen kanssa. Kolmanneksi vähäinen kysyntä artikla 9-rahastoille erityisesti yksityissijoittajien keskuudessa, jotka eivät usein erota SFDR-kategorioita toisistaan, vähentää entisestään kannustimia sen tavoitteluun. Sen sijaan artikla 8 nähdään turvallisempana ja kaupallisesti toimivampana vaihtoehtona, sillä se tarjoaa enemmän joustavuutta kestävyystekijöiden määrittelyssä ja soveltamisessa. Havaintojen perusteella nykyiset markkinarakenteet ja sääntelyn epäselvyys voivat rajoittaa SFDR:n tehokkuutta sen tavoittelemien kestävyysvaikutusten saavuttamisessa.
Keywords: sustainable finance, ESG investing, SFDR